The digestion of galactolipids and its ubiquitous function in Nature for the uptake of the essential α-linolenic acid. Issue 8 (20th July 2020) - Sahaka, Moulay; Amara, Sawsan; Wattanakul, Jutarat; Gedi, Mohamed A.; Aldai, Noelia; Parsiegla, Goetz; Lecomte, Jérôme; Christeller, John T.; Gray, David; Gontero, Brigitte; Villeneuve, Pierre; Carrière, Frédéric
Abstract : Galactolipases allow the digestion of galactolipids, the most abundant lipids on Earth and the main source of α-linolenic acid. Abstract : Galactolipids, mainly monogalactosyl diglycerides and digalactosyl diglycerides are the main lipids found in the membranes of plants, algae and photosynthetic microorganisms like microalgae and cyanobacteria. As such, they are the main lipids present at the surface of earth. They may represent up to 80% of the fatty acid stocks, including a large proportion of polyunsaturated fatty acids mainly α-linolenic acid (ALA). Nevertheless, the interest in these lipids for nutrition and other applications remains overlooked, probably because they are dispersed in the biomass and are not as easy to extract as vegetable oils from oleaginous fruit and oil seeds. Another reason is that galactolipids only represent a small fraction of the acylglycerolipids present in modern human diet. In herbivores such as horses, fish and folivorous insects, galactolipids may however represent the main source of dietary fatty acids due to their dietary habits and digestion physiology. The development of galactolipase assays has led to the identification and characterization of the enzymes involved in the digestion of galactolipids in the gastrointestinal tract, as well as by microorganisms. Pancreatic lipase-related protein 2 (PLRP2) has been identified as an important factor of galactolipid digestion in humans, together with pancreatic carboxyl ester hydrolase (CEH). The levels of PLRP2 are particularly high in monogastric herbivores thus highlighting the peculiar role of PLRP2 in the digestion of plant lipids. Similarly, pancreatic lipase homologs are found to be expressed in the midgut of folivorous insects, in which a high galactolipase activity can be measured. In fish, however, CEH is the main galactolipase involved. This review discusses the origins and fatty acid composition of galactolipids and the physiological contribution of galactolipid digestion in various species. This overlooked aspect of lipid digestion ensures not only the intake of ALA from its main natural source, but also the main lipid source of energy for growth of some herbivorous species.